Surface Chemistry in Environmental Degradation of Polymeric Solids - An, Yingjun (Langmuir : the ACS journal of surfaces and colloids, 2024)
Microplastics (MPs) cause significant adverse environmental effects. To address this issue, a scientific approach for understanding the formation of MPs is essential. In this Perspective, we summarize the three typical degradation behaviors of polymeric solids from a surface chemistry perspective: chemical degradation, biodegradation, and mechanical degradation. These three degradation processes can occur consecutively or simultaneously in poorly managed polymeric materials, ultimately resulting in their disintegration into the environment. This Perspective provides valuable insights into controlling the degradation of polymeric solids and designing eco-friendly polymers for a sustainable future